Study of general toxic effect of bacteriosens in rodents and large laboratory animals - N. B. Morozova; A. A. Pankratov; E. A. Plotnikova; M. S. Vorontsova; E. A. Makarova; E. A. Lukyanets; A. D. Kaprin (Исследования и практика в медицине, 2019)
Purpose of the study. The objectives of the research are to evaluate the potential toxicity of Bacteriosens when administered to animals once only («acute» toxicity) or repeatedly («chronic» toxicity) and to study its biocompatibility with blood components.Materials and methods. Bacteriosens is the medicine on the basis of photoactive compound of mezo-tetra (3-pyridyl) bacteriochlorin with λmax of 747 nm. Ex vivo study of its biocompatibility with blood components included the evaluation of the impact of the solution on the coagulability of non-stabilized venous blood. The in vitro method of detecting erythrocyte osmotic resistance to hemolytic ability of Bacteriosens was used. The «acute» toxicity was studied in F1 hybrid mice (CBA x C57Bl/6j) and non-bred rats, male and female, after single intravenous and intraperitoneal injections of Bacteriosens. The «chronic» toxicity was studied in non-bred rats, male and female, and Soviet Chinchilla rabbits after multiple intravenous injection of the drug (over the period of 14 days). Time period before toxicity-induced death of animals, clinical signs of intoxication, and the impact of the medicine on the inner organs and body systems were evaluated using physiologic and pathophysiologic, clinical, and laboratory methods.Results. Incompatibility of non-stabilized rat blood with Bacteriosens after the incubation with the medicine in concentrations varying from 0.5 till 0.005 mg/ml has not been discovered. The aquatic solution of Bacteriosens should be injected into animals and later on into humans slowly or by drip feed in concentrations not exceeding 0.5 mg/ml. A single injection of Bacteriosens in doses from 5.0 to 50.0 mg/kg and from 1.3 to 20.8 mg/kg to mice and rats (male and female), respectively, was tolerated by the animals satisfactorily. No toxicity-induced deaths or skin phototoxicity have been detected. The studied doses of Bacteriosens in mice 25-250 times exceeded the calculated equitherapeutic dose for humans, and in rats, 6.5-104 times. Bacteriosens in total doses from 18.2 to 72.8 mg/kg and from 8.3 to 33 mg/kg administered as multiple intravenous injections for 14 days to rats and rabbits respectively, did not induce the death of the animals and demonstrated no toxic impact on blood, liver, kidneys, heart, hemostasis system, or central nervous system. The drug did not adversely affect carbohydrate and lipid metabolism.Conclusion. Bacteriosens when administered as a single dose or as multiple injections in the range of studied doses did not have adverse toxic effect on mice, rats, and rabbits. The studied doses of Bacteriosens in rats 91-364 times exceeded the calculated equitherapeutic dose for humans, and 41-165 times, in rabbits.